Propiedades fisicas e hidrodinamica de la fluidizacion del cafe verde y tostado (Coffea arabica L. var. typica) - Sanchez Ramirez, J.=700 1 Anaya Soza, I.; Vizcarra Mendoza, M.G.; Gutierrez Lopez, G.; Santiago Pineda, T.
(En, Es)
ilus., 17 ref.
Keywords: CAFE; PROPIEDADES ORGANOLEPTICAS; PROPIEDADES FISICO-QUIMICAS; TOSTADO; TRATAMIENTO EN LECHO FLUIDO; MEXICO